Algeria match مرتكزات الصحافة الالكترونية المتخصصة في الجزائر دراسة تحليلية لصحيفة - بلال دادي; عادل شكيمة (جامعة الوادي - University of Eloued, 2025)
"هدفت الدراسة إلى تحديد أهم المرتكزات في الصحافة الالكترونية المتخصصة بالجزائر وذلك من خلال القيام بدراسة مسحية تحليلية على صحيفة Algeria match ، وصنفت دراستنا ضمن الدراسات الوصفية، وتم الاعتماد على المنهج المسحي، كما قدر حجم العينة ب 23 مفردة مست كل أيام الأسبوع ومستخدمين بذلك العينة القصدية العرضية، وتوصلت الدراسة إلى النتائج التالية: ركزت الصحيفة الرياضية Algeria match على المواضيع الاعلامية التي تتسم بالحيوية والفاعلية من خلال تصريحات مختلف الأطراف الرياضية وانطباعاتهم حول القضايا الرياضية، واهتمت الصحيفة الرياضية محل الدراسة بالأخبار المحلية والوطنية بشكل كبير لتجسيد القرب الاجتماعي وتكريس الهوية الوطنية. بينت الصحيفة الجزائرية في فئة الشخصيات الفاعلة عن توجهها البالغ الابراز اللاعبين والمسؤولين في المضامين الصحفية باعتبارهم محور الأحداث الرياضية. أبانت صحيفة Algeria match عن مدى اعتمادها الكبير في ابراز سياستها التحريرية الخاصة من خلال التحرير المركزي. برزت مفاهيم التنافس والتحدي بشكل كبير في مضامين الصحيفة من خلال اتسام مختلف محتوياتها بقيمة المنافسة، كما اعتمدت الصحيفة الرياضية على فني الخبر والتقرير بكثرة وذلك لتقديم المواد الاعلامية لجمهورها بأسلوب سهل وواضح وبسيط. ركزت الصحيفة على النموذج التقليدي في فئة القوالب من خلال اعتمادها على القوالب التقليدية ممثلة بالهرم المقلوب كأكثر نسبة واهمالها بشكل شبه كلي للقوالب الحديثة، اكتفت بالصور الثابتة في المضامين الاعلامية مع اهمالها لبقية الوسائط المتعددة، و أتاحت الصحيفة مختلف الوسائط التفاعلية من خلال توفر امكانية التعليق والمشاركة والتفاعل في المحتوى. أبانت الصحيفة محل الدراسة عن توجهها اللغوي وذلك بتوظيف اللغة العربية الفصحى بشكل كبير مما يساهم في تعزيز الهوية اللغوية. اعتمدت الصحيفة على العناوين الرئيسية والفرعية معا بشكل مبالغ من أجل تبسيط المعنى وتسهيله للقارئ. أبانت الصحيفة عن الحضور المحتشم لوسائطها الاتصالية من خلال عدم امكانية الوصول المواقع التواصل الاجتماعي ما عدى الفايسبوك وعدم امكانية الوصول لرقم الفاكس" "The study aimed to identify the most important pillars of specialized electronic journalism in Algeria by conducting an analytical survey of the newspaper Algeria Match. Our study was classified as a descriptive study, and the survey method was used. The sample size was estimated at 23 items covering all days of the week, using a purposive cross-sectional sample. The study reached the following results: The sports newspaper Algeria Match focused on lively and effective media topics through the statements of various sports parties and their impressions of sports issues. The sports newspaper under study focused greatly on local and national news to embody social proximity and consolidate national identity. In the category of influential figures, the Algerian newspaper demonstrated its strong tendency to highlight players and officials in journalistic content, considering them the focus of sporting events. The newspaper Algeria Match demonstrated the extent to which it relies heavily on highlighting its own editorial policy through central editing The concepts of competition and challenge were prominent in the newspaper's content, as its various contents were characterized by competitive values. The sports newspaper also relied heavily on the art of news and reporting to present media materials to its audience in an easy, clear, and simple manner. The newspaper focused on the traditional model in the template category, relying on traditional templates represented by the inverted pyramid as the largest percentage, and almost completely neglecting modern templates. It was satisfied with static images in the media content, while neglecting the rest of the multimedia. The newspaper provided various interactive media by providing the possibility of commenting, participating, and interacting with the content. The newspaper under study demonstrated its linguistic orientation by employing the classical Arabic language extensively, which contributes to strengthening linguistic identity. The newspaper relied on both main and subheadings in an exaggerated manner in order to simplify the meaning and make it easier for the reader. The newspaper demonstrated the modest presence of its communication media, as it was unable to access social networking sites except for Facebook and the inability to access the fax number."
مذكرة ماستر قسم اعلام واتصال تخصص سمعي بصري
Keywords: الصحيفة; الصحافة المتخصصة; الصحافة الالكترونية; مرتكزات; Electronic Journalism; Specialized Journalism; Newspaper